All for the children : multicultural essentials of literature - Finazzo, Denise Ann. (Albany, N.Y. : Delmar, 1997)
This book is divided into three parts: Children's Literature: A history and definition; Integration of children's literature that is multicultural; and Curricular applications of multicultural literature.
Keywords: Multiculturalism; Children's literature; Multiculturalism; Children's literature -- History and criticism